(untitled) (Journal of the College of Basic Education, 2025)
Human beings live under multiple influences and are constantly faced with interactive situations that require innovation as a fundamental condition for achieving adaptation in a rapidly changing world. In light of the increasing accumulation of knowledge and ongoing scientific and technological development, it becomes essential to continuously seek out information, knowledge, and facts in order to face various challenges and situations. This reality necessitates possessing a flexible cognitive style and an open mindset that embraces innovation and development within a broad intellectual framework (Al-Saadi, 1982, p. 9). Personal effectiveness is one of the essential traits in shaping a well-adjusted personality, as it is linked to an individual’s sense of responsibility in various areas of life—towards family, colleagues, neighbors, and society at large. This effectiveness contributes to enhancing interaction with others and plays a pivotal role in the processes of acquiring and retaining knowledge, acting as an internal drive and primary guide without which the learning process cannot be complete (Yusuf, 2016, p. 3). Spiro (1995) defined cognitive flexibility as an individual’s ability to continuously construct and modify mental representations and generate multiple alternatives based on the stimuli and available information in a given situation. This ability includes adapting cognitive responses to process new and unexpected situations, understanding the internal relationships between things and concepts, and recognizing similarities and differences among them (Spiro, 1995, p. 169). Bandura (1997) defined Personal effectiveness refers to the individual’s ability to perform behaviors that achieve desired outcomes in specific situations and to control events that affect their life by forming self-expectations about how to carry out tasks and activities. Thus, perseverance represents a practical aspect of self-efficacy, driving the individual toward continuous and positive engagement with assigned tasks, despite any difficulties or pressures faced (Bandura, 1997, p. 192). The present study aims to explore the following: The level of cognitive flexibility among students of the Department of Psychological Counseling and Educational Guidance. The level of personal effectiveness among students of the Department of Psychological Counseling and Educational Guidance. The statistically significant correlation between the level of cognitive flexibility and personal effectiveness among students of the Department of Psychological Counseling and Educational Guidance. The study was conducted on a sample of 100 male and female students from the Department of Psychological Counseling and Educational Guidance, evenly divided into 50 males and 50 females. A random sampling technique was adopted to ensure fair representation of the research population. The researcher constructed a scale for measuring cognitive flexibility among the students, consisting of 27 items, each with five response options, based on Spiro’s (1995) theory of cognitive flexibility. Additionally, the researcher adopted a scale of personal effectiveness from Lina’s thesis (2022), which included 32 items with five response options each .The researcher verified the psychometric properties of both scales, including face validity and indicators of construct validity, through the correlation of each item with the total score of the scale. Reliability was assessed using Cronbach’s Alpha coefficient. The results confirmed the scales’ effectiveness in measuring the intended variables. After applying the scales to the research sample, data were processed using statistical methods, including the one-sample t-test and the independent samples t-test and Pearson Correlation Coefficient. The findings revealed that the research sample students of the Department of Psychological Counseling exhibited a low level of cognitive flexibility and a high level of personal effectiveness. Moreover, a Negative correlation was found between cognitive flexibility and personal effectiveness. Based on these results, the researcher proposed a set of conclusions, recommendations, and suggestions for future research.